Players and arenas: strategic interactionism in social movements studies. (1st November 2016) - McGarry, Aidan; Davidson, Robert J.; Accornero, Guya; Jasper, James M.; Duyvendak, Jan Willem
Abstract: This 'Authors Meet Critics' symposium focuses on two books edited by Jan Willem Duyvendak and James M. Jasper, Players and Arenas: The Interactive Dynamics of Protest and Breaking Down the State: Protestors Engaged . Both books make bold attempts to develop and apply a strategic interactionist perspective in social movement studies by focusing on the interplay of micro and macro processes and decision-making in a range of protest movements. Critical interventions from Aidan McGarry, Robert J. Davidson and Guya Accornero raise a number of questions relating to the core arguments of the books, the key findings and the conceptual advances. Duyvendak and Jasper then address these challenges by drawing attention more acutely to the role of agency in social movements and highlighting significant critiques of the current state of the art in social movement scholarship.